The Imperforate Hymen: A Case Report on A Modern Hymenectomy Incision Method - Erika Kusumawardani; M. Ali Sabisi; Adrian Desmar Pardomuan Ringo Ringo (Asian Journal of Health Research, 2026)
Introduction: An imperforate hymen is a congenital condition in which the hymen completely obstructs the vaginal canal. Many patients remain asymptomatic until menarche, when they may present with primary amenorrhea, a pelvic mass, and cyclic abdominal pain. The traditional hymenectomy technique involves a cruciate (cross-shaped) incision with excision of the quadrants and approximation of the hymenal edges to the vestibule using absorbable sutures. However, this method can be associated with scar formation and subsequent reclosure of the hymen. Case Presentation: A 12-year-old girl presented with cyclic abdominal pain for three months, which worsened one week prior to admission. She complained of severe abdominal pain starting six hours before hospital admission. Physical examination revealed a palpable lower abdominal mass, tenderness, and no visible hymenal opening. Ultrasonography showed hematometra and hematocolpos, leading to the diagnosis of imperforate hymen. The patient underwent an annular hymenectomy using electrocautery to create a circumferential (ring-shaped) excision, aiming to prevent postoperative hymenal closure and scarred hymenal contour. Conclusion: Imperforate hymen should be considered in premenarcheal adolescent girls presenting with cyclic abdominal pain. Annular hymenectomy using electrocautery offers a modern surgical approach that may reduce postoperative hymenal reclosure and scarring compared with the traditional cruciate technique.